S-curve and landscape maps for the analysis of trends on industrial textile wastewater treatment (2024)
The textile industry is one of the most important and economically significant industries in the world. China is the largest textile producer, for countries such as India, Pakistan, Bangladesh and Malaysia this sector is of crucial importance and it is also a growing sector in Latin America. This industry is responsible for 10 % of annual global carbon emissions and 20 % of global wastewater. This figure is worrying as this wastewater is highly recalcitrant, which has led to research into different treatment methods that are efficient and can provide a sustainable solution to this problem. The aim of this literature review was to identify the existing methods for the treatment of dry scrubber wastewater (TWWT) and the effects of this wastewater and its composition, focusing on biological, chemical and physicochemical processes from the point of view of advantages and disadvantages. It was analyzed which are the most important scientific areas of TWWT and which countries are the most important in this field, as well as the primary pollutants and TWWT processes. Finally, this analysis provides a context for current trends in TWWT research. In general, coagulation methods have been found to be fast but present difficulties due to the use of toxic coagulants; advanced oxidation processes (AOPs) are positioned as very effective methods that can disinfect and decontaminate these effluents. Currently, biological systems coupled with AOPs are a growing trend. Microalgae and cyanobacteria processes coupled with AOPs have attracted great interest due to the possibility of obtaining high added value products through the biorefining of biomass.